Wogonin protects against bleomycin-induced mouse pulmonary fibrosis via the inhibition of CDK9/p53-mediated cell senescence - Wang, Libo; Lin, Fei; Liu, Youli; Li, Wei; Ding, Qingjie; Duan, Xulei; Yang, Lin; Bai, Zhengyu; Zhang, Min; Guo, Yuming (Frontiers in Pharmacology, 2024)
Pulmonary fibrosis (PF) is a fatal interstitial lung disease associated with declining pulmonary function but currently with few effective drugs. Cellular senescence has been implicated in the pathogenesis of PF and could be a potential therapeutic target. Emerging evidence suggests wogonin, the bioactive compound isolated from Scutellaria baicalensis, owns the antisenescence properties, however, the possible impact of wogonin on PF and the potential mechanisms remain unclear. In this study, a well-established mouse model of PF was utilized which mice were administrated with bleomycin (BLM). Strikingly, wogonin treatment significantly reduced fibrosis deposition in the lung induced by BLM. In vitro, wogonin also suppressed fibrotic markers of cultured epithelial cells stimulated by BLM or hydrogen peroxide. Mechanistic investigation revealed that wogonin attenuated the expressions of DNA damage marker γ-H2AX and senescence-related markers including phosphorylated p53, p21, retinoblastoma protein (pRB), and senescence-associated β-galactosidase (SA-β-gal).Moreover, wogonin, as a direct and selective inhibitor of cyclin-dependent kinase 9 (CDK9), exhibited anti-fibrotic capacity by inhibiting CDK9 and p53/p21 signalling. In conclusion, wogonin protects against BLM-induced PF in mice through the inhibition of cell senescence via the regulation of CDK9/p53 and DNA damage pathway. This is the first study to demonstrate the beneficial effect of wogonin on PF, and its implication as a novel candidate for PF therapy.